MINIMIZING TRADITIONAL APPROACH IN INDONESIAN EDUCATION - Musdiani (Jurnal Visipena, 2013)
This essay discusses the traditional approach in Indonesian education from different angle; cause and effect perspective. A traditional teaching approach employs a didactic flow of knowledge from the teacher, as a sage, to the student as a receptacle (Richmond, 2007) which more emphasizes the mastery of concept, with less stress on skills improvement. The common system of traditional education is teacher centred where the teacher focuses on delivering information about some contents (Liang, 2004). Teacher-centred class instruction and rote learning are deeply embedded; this type of instruction has become a part in the Indonesian school culture and unofficial standard of practice for years (USAID 2008; Bjork 2005). Shallow level of meaning found in school science (Aikenhead 2000). There are several explanations related to these problem; the institutional culture, the Indonesian school cultures; standardized and highly centralized examinations, and less emphasize on improving their teaching ability. Due to these causes, this paper proposes 4 solutions as follows; first, detaching the teachers from their dependence on and deference to the policies and regulations of the central government’s education authorities, Second, finding other methods of teacher recruitment, third, empowering the teachers: enriching pedagogical knowledge-lesson study/action research, and prosperity, last, providing a fair system which is emphasized on teaching Standard for standardized test.